2009
DOI: 10.1007/s00192-009-1007-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical strategies for women with pelvic organ prolapse and urinary stress incontinence

Abstract: No differences were found between the two treatment strategies, but almost one third of women were cured of SUI by prolapse surgery alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 27 publications
2
80
0
3
Order By: Relevance
“…9 That study by Borstad et al showed more benefit from combination surgery than seen in our trial. Two differences between the studies might explain the lower percentage of women undergoing additional MUS after index surgery (57% versus 17% in our trial).…”
Section: Discussionmentioning
confidence: 37%
See 2 more Smart Citations
“…9 That study by Borstad et al showed more benefit from combination surgery than seen in our trial. Two differences between the studies might explain the lower percentage of women undergoing additional MUS after index surgery (57% versus 17% in our trial).…”
Section: Discussionmentioning
confidence: 37%
“…A meta-analysis of the pooled complication rates of the Borstad et al study and the OPUS trial also showed slightly more adverse events in the MUS group (15% versus 10%; RR 1.6; 95% CI 1.0-2.5). 4,9,24 Obviously, additional procedures will increase the risks of expected complications. However, the rate of severe complications in our study was higher than one would expect from simply adding the complication risk of MUS to POP surgery alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the previous studies implied that concomitant prophylactic surgery caused better surgical outcomes. In contrast, there was no statistically signifi cant difference of concomitant surgery according to the study of Borstad et al [14] but the prevalence of postoperative SUI was less in the group who had concomitant surgery than the group who had no concomitant surgery. However 27% (almost one third) of patients were cured of SUI by prolapse surgery alone, which meant that some preoperative SUI could be corrected by only prolapse surgery.…”
Section: Discussionmentioning
confidence: 84%
“…However, after the additional insertion of a suburethral tape, 235 out of 237 women (99 %) were continent postoperatively [87,[127][128][129]. One randomized study investigated the question whether treatment should be carried out as a one-stage or a two-stage procedure; it was found that the treatment of stress incontinence was equally successful, irrespective of whether the suburethral TVT was inserted at the same time as the anterior vaginal wall repair (83/87, 95%) or three months later (47/53, 89%; based on an ontreatment analysis) [130]. However, 27/94 women (29%) were continent following prolapse surgery alone and refused the planned TVT procedure three months later [130].…”
Section: Women With Symptomatic Stress Urinary Incontinence and Genitmentioning
confidence: 99%